2019
DOI: 10.3390/ma12030384
|View full text |Cite
|
Sign up to set email alerts
|

Compression Strength Mechanisms of Low-Density Fibrous Materials

Abstract: In this work we challenge some earlier theoretical ideas on the strength of lightweight fiber materials by analyzing an extensive set of foam-formed fiber networks. The experimental samples included various different material densities and different types of natural and regenerated cellulose fibers. Characterization of the samples was performed by macroscopic mechanical testing, supported by simultaneous high-speed imaging of local deformations inside a fiber network. The imaging showed extremely heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 30 publications
(55 reference statements)
1
47
0
Order By: Relevance
“…12 ). According to Ketoja et al [ 16 ], when a random fibre network is compressed, the buckling continues throughout the compression cycle, up to the densification regime. This results from an exponential distribution of fibre-segment lengths, valid also for flocculated networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 ). According to Ketoja et al [ 16 ], when a random fibre network is compressed, the buckling continues throughout the compression cycle, up to the densification regime. This results from an exponential distribution of fibre-segment lengths, valid also for flocculated networks.…”
Section: Discussionmentioning
confidence: 99%
“…Gibson and Ashby considered the compression of cellular structures and found that the individual columns buckle when the applied force, , reaches a critical level [ 17 ] given by Euler’s formula Here E is the elastic modulus, I is the cross-sectional moment of inertia, a is the free-span length of the column and is a pre-factor which depends on the boundary conditions at the column ends. Effectively, this is the same formula as for fibre buckling [ 16 ], but the distribution of column lengths for the more correlated cellular structure probably differs from the exponential distribution of the fibre segments. Kim et.al.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical fiber orientation is caused by the direction of foam flow in filling the mold. (b) A small part of a thick plate-like sample [126] with natural wood fibers (density 60 kg/m 3 ). (c) Sheet with CTMP fibers (density 111 kg/m 3 ).…”
Section: Materials Densitymentioning
confidence: 99%
“…For example, in [72], a theory has been developed, that describes the statistical properties of rod packings, while taking into account that the deposited rods cannot overlap and thus induce steric hindrances. Further, a new buckling theory including a statistical distribution of free-span lengths has been proposed in [130] and tested against experimental data.…”
Section: Random Fiber Networkmentioning
confidence: 99%